PENINGKATAN AKTIVITAS DAN HASIL BELAJAR SISWA MELALUI PEMBELAJARAN TEAMS GAMES TOURNAMENS - Tiyas Puji Rahayu; Wahjoedi Wahjoedi; Sudarmiatin Sudarmiatin (Graduate School of Universitas Negeri Malang, 2017)
The research was classroom action research that aims to describe the implementations of TGT learning to increased the activity and learning outcomes of fourth grades in SDN Sidokaton Kudu Jombang. The research did on two cycles. Each of the cycle consisted of four meetings. The date collected through observation sheets of students activity and the test results of students learning. The results of the research which an increased of the students activity in the first cycle of 70% students is active and very active and increased in the second cycle of 90%. The result of classical learning competences in the first cycle of 65% increased in the second cycle of 85%.Penelitian ini adalah penelitian tindakan kelas yang bertujuan mendeskripsikan penerapan pembelajaran TGT untuk meningkatkan aktivitas dan hasil belajar siswa kelas IV SDN Sidokaton Kudu, Jombang. Penelitian dilaksanakan dalam dua siklus. Setiap siklus terdiri atas empat pertemuan. Pengumpulan data melalui hasil observasi aktivitas siswa dan tes hasil belajar siswa. Hasil penelitian menunjukkan peningkatan aktivitas belajar siklus I sebesar 70% siswa aktif dan sangat aktif meningkat siklus II sebesar 90%. Ketuntasan belajar klasikal siswa siklus I sebesar 65% meningkat siklus II sebesar 85%.